International Law Issues Concerning Marine Environment Protection in the Arctic - Sorokina, T. Yu (Moscow journal of international law, 2024)
INTRODUCTION. The Arctic is a unique marine and terrestrial ecosystem. However, the Arctic region is currently experiencing enormous environmental stress. This is due to the following factors. The ﬁrst factor is the ongoing climate change on the planet as a whole, which is most clearly seen in the Arctic. Researchers claim that some species of ﬂora and fauna are threatened with extinction. For example, the polar bear, the largest specie in the Arctic trophic chain, is currently experiencing great diﬃculties in ﬁnding food due to the abundant melting of glaciers and, as a result, the reduction of its habitat. Global warming is also causing changes in habitats and migration routes not only for Arctic species, but also for other species that have never climbed so high to the north. Nowadays, local ﬁshermen sometimes catch species of ﬁsh that have never been seen in Arctic waters before. Cases of Paciﬁc salmon entering the Atlantic Ocean through the Arctic seas have also been recorded. There is another problem related to the climate factor. For many years, a huge amount of toxic waste has been stored in the Arctic coastal areas. Due to the melting of permafrost, pollutants enter the marine ecosystem, accumulate in marine biota and as a result end up on our table. The second factor is the increased anthropogenic impact due to both climate change and the Arctic political strategies of several states at once. The development of the Northern Sea Route (NSR), the increase in the intensity of navigation, exploration and extraction of natural resources, construction of infrastructure facilities and other human activities have a negative impact on the environment. The Arctic ecosystem is facing an increase in production and consumption waste [Kallenborn, Brorstrom-Lunden, Reiersen, Wilson 2018:33001; Jaskolski, Pawlowski, Strzelecki, Zagorski, Lane 2018:2011], noise [Quijano, Hannay, Austin 2019:1228; Stevenson, Davies, Huntington, Sheard 2019:83; Kyhn, Sveegaard, Tougaard 2014:424], light [Ludvigsen, Berge, Geoﬀroy, Cohen, De La Torre, Nornes, Singh, Sorensen, Daase, Johnsen 2018; Bennie, Duﬀy, Davies, Correa-Cano, Gaston 2015:2715], vibration, temperature, chemical and biological pollution. The risk of man-made accidents and catastrophes increases, which can lead to even more dangerous consequences. MATERIALS AND METHODS. We have studied and analyzed international agreements and other documents on the protection of the Arctic marine environment. The texts of these documents were taken for analysis on the oﬃcial pages on the Internet. Such resources include, for example, the oﬃcial website of the United Nations Organization (UN), the International Maritime Organization (IMO), etc. Work with Russian legal acts included access to such portals as the oﬃcial website of the Government of the Russian Federation, the Administration of the Northern Sea Route, the ConsultantPlus Legal Reference System, etc. The international documents were divided into groups, which are presented in a separate table. This made it possible to structure the work, avoid long lists in the text and focus on the most important aspects of the topic under consideration. The research is also based on published works of experts in the ﬁeld of International law, law of the sea, environmental law, political science, environmental science and other ﬁelds of knowledge. Web of Science (webofknowledge. com), Russian scientiﬁc electronic library (elibrary. ru), Researchgate (researchgate.net) and other systems became the resources for working with literature. The author also studied law enforcement practice, trends in the development of scientiﬁc research in the region, as well as some political processes that are somehow related to the modern legal regulation of marine environment protection in the Arctic. The term “Arctic states” is used in this article as it is given in the [Vylegzhanin 2013]. The term “coastal States” is used in this article as it is given in the 1982 UN Convention on the Law of the Sea. RESEARCH RESULTS. As a result of ongoing climate changes on the planet, as well as due to increased anthropogenic pressure on the region, the fragile ecosystem of the Arctic is currently subject to various types of pollution (noise, vibration, light, radioactive, various types of waste, etc.) and degradation. Both scientists and politicians pay attention to this. We have analyzed the existing international and national norms, regulating relations for the protection of the Arctic marine environment. For these purposes, international documents, depending on the range of regulated issues, were divided into ﬁve groups: 1) general; 2) special; 3) agreements regulating liability and compensation issues; 4) environmental agreements that indirectly regulate the protection of the marine environment; 5) Arctic documents. It is determined that the 1982 UN Convention on the Law of the Sea (hereinaﬅer referred to as the Convention of 1982) is one of the main “general” agreements, which not only establishes the obligations of participating countries to protect the marine environment, but also provides coastal states with special environmental requirements in ice–covered areas, including the Arctic Ocean. In this regard, the Russian Federation has undertaken an obligation to regulate navigation in the waters of the Northern Sea Route (hereinaﬅer – the NSR) for the purposes of environmental protection and prevention of pollution from ships. The issue of the need to develop and sign a separate agreement on the Arctic was also considered by the author, and the conclusion was formulated that there is no need and objective possibility of implementing such an initiative, especially in the current political situation in the world. The author notes that all specialized international Arctic documents have an ecocentric focus, which meets the intentions of the Arctic states, including Russia, to continue the development and development of Arctic territories and waters with mandatory compliance with modern environmental requirements. In this regard, the development of scientiﬁc research in the Arctic and the improvement of the best existing environmental technologies are of particular importance. The 2017 Agreement on Strengthening International Arctic Scientiﬁc Cooperation is designed to promote the development of joint research and information exchange. However, in light of the suspension of scientiﬁc and technical cooperation between the Russian Federation and other Arctic states, we cannot consider its eﬀectiveness today. DISCUSSSION AND CONCLUSIONS. There is a large number of documents regulating the protection of the Arctic marine environment, which have been developed at the international level. The Arctic ecosystem needs special protection because of its vulnerability. The ongoing climate change and melting of glaciers have led to an increase in anthropogenic pressure on the region. At the same time, it is known that any human activity has a negative impact on the state of the environment. Despite the existence of a large number of international and national documents on the protection of the Arctic marine environment, many issues have not yet been resolved. Today we face the need to ﬁll in the existing gaps. However, the development of regulatory documents should be based on the results of scientiﬁc research in various ﬁelds of knowledge. This will ensure the validity of the decisions made. The Arctic is subject to international regulation, and the fragile Arctic environment is also protected internationally. The Arctic region diﬀers from the Antarctic: the Antarctic Treaty eﬀectively freezes territorial claims to the South Pole and allows states to protect the environment. The land part of the Arctic belongs to eight Arctic states. Therefore, international cooperation in the Arctic region faces many challenges, and the norms of nternational law, such as the 1982 UN Convention on the Law of the Sea, are necessary to resolve emerging disputes.